Anaerobic regulation of transcription initiation in the arcDABC operon of Pseudomonas aeruginosa. - Gamper, M (1991)
The arcDABC operon of Pseudomonas aeruginosa encodes the enzymes of the arginine deiminase pathway, which is inducible under conditions of oxygen limitation and serves to generate ATP from arginine. The 5' end of arc mRNA extracted from anaerobically grown cells was determined by S1 and primer extension mapping. The transcription initiation site was located upstream of the arcD gene and 41.5 bp downstream of the center of the sequence TTGAC....ATCAG. This sequence, termed the ANR box, is similar to the consensus FNR recognition site of Escherichia coli. Transcription of the arc operon in P. aeruginosa was strongly decreased by a deletion of the TTGAC half site or by a mutation in the anr gene, which is known to code for the FNR-like regulatory protein ANR. During a transition from aerobic to anaerobic growth conditions, the concentrations of arc mRNAs and the levels of the ArcD and ArcA proteins rose in a parallel fashion. Mutational analysis of the arc promoter region led to the conclusion that the distance between the ANR box and the -10 promoter region is important for promoter strength, whereas the -35 region does not appear to be critical for arc promoter function. These findings and previous results indicate that anaerobic induction of the arc operon occurs at the level of transcription and requires the ANR box in cis and the ANR protein in trans.